USE OF HEAT AND ENVIRONMENT ENERGY RADIATION BASED ON EXERGY ANALYSIS FOR ENERGY SAVING IN THE AGRO-INDUSTRIAL COMPLEX AND HOUSING AND COMMUNAL SERVICES - Sventitsky, A.; Sventitsky, I.; Korolev, V. (Енергетика і автоматика, 2016)
The significant reduction to energy capacity to agricultural product and gross product to Russia possible to reach efficient use on base exergy analysis of the heat of the ambience and energy of the solar radiation. The expenseses fuel on heat processes decrease in 2,5-3 times herewith.